Hebella Allman 1888 - Soto, Joan J.; Peña, Álvaro L. (Zenodo, 2019)
Hebella cf. plana (Ritchie, 1907) (Fig. 6n) Material examined. ANT XV/3 : PS65/77 , few hydrothecae, on A. frigida . Remarks. In our material, the length of the hydrotheca is 1440–1600 µm, the diameter at the aperture is 411– 431 mm, and the diameter at diaphragm 280–312 µm. The length of the pedicel is 115 µm. These measurements are considerably larger than those given by Peña Cantero et al. (2004), and therefore we are not entirely confident with its specific assignation. Ecology and distribution. Known from depths between 92 (Peña Cantero 2008) and 722 m (Peña Cantero et al. 2004); present material came from depths between 340 and 360 m. Species with Antarctic-Patagonian distribution (Peña Cantero et al. 2004). Published as part of Soto, Joan J. & Peña, Álvaro L., 2019, Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica), pp. 1-78 in Zootaxa 4570 (1) on page 24, DOI:10.11646/zootaxa.4570.1.1, http://zenodo.org/record/2608527